Low-level mixing height detection in coastal locations with a scanning Doppler lidar - Vakkari, V.; O'Connor, E. J.; Nisantzi, Argyro; Mamouri, Rodanthi-Elisavet (My University, 2015)
Mixing layer height (MLH) is one of the key parameters in describing lower tropospheric dynamics and capturing its diurnal variability is crucial, especially for interpreting surface observations. In this paper we introduce a method for identifying MLH below the minimum range of a scanning Doppler lidar when operated at vertical. The method we propose is based on velocity variance in low-elevation-angle conical scanning and is applied to measurements in two very different coastal environments: Limassol, Cyprus, during summer and Loviisa, Finland, during winter. At both locations, the new method agrees well with MLH derived from turbulent kinetic energy dissipation rate profiles obtained from vertically pointing measurements. The low-level scanning routine frequently indicated non-zero MLH less than 100 m above the surface. Such low MLHs were more common in wintertime Loviisa on the Baltic Sea coast than during summertime in Mediterranean Limassol.
Keywords: Coastal locations; Scanning Doppler lidar; Tropospheric dynamics; Mixing layer height (MLH)